Use of single IRBs for multi-site studies: A case report and commentary from a National Drug Abuse Treatment Clinical Trials Network study - Nichols, Ceilidh; Kunkel, Lynn E.; Baker, Robin; Jelstrom, Eve; Addis, Megan; Hoffman, Kim A.; McCarty, Dennis; Korthuis, P. Todd (Contemporary clinical trials communications, 2019)
Recent NIH policy stipulates that multi-site studies must use a single or IRB (Institutional Review Board) in order to streamline the review process while maintaining standards for human subjects protection. The Western States Node of the Clinical Trials Network (CTN) used a single IRB for protocol CTN-0067, a clinical trial testing the use of an opioid antagonist (extended-release naltrexone) versus opioid agonists (buprenorphine or methadone) for opioid use disorders among individuals living with HIV. This case study discusses the processes and challenges associated with use of a single IRB. These lessons are also informed by other single IRB experiences within the CTN. The intention of the NIH single IRB policy is to facilitate efficient IRB processes. Advanced planning and transparent communication, however, are critical to avoid stalling IRB approval and protocol implementation. Research teams need to account for local IRB willingness to cede to a single IRB and understand the variations in interpretations of abbreviated reviews. In order to facilitate the effective use of single IRBs, recommendations include assigning staff at each study site for IRB submission coordination and interaction with the lead site IRB staff, training investigators and key regulatory staff on expectations for working with single IRBs, dedicating a regulatory specialist at the lead site to manage the process, developing a communication plan, and supporting the development of strong working relationships with local regulatory staff and the single IRB. The CTN experiences with single IRBs may provide insights for other investigators.